ESRA19-0190 A cadaveric study of ultrasound-guided inferior alveolar nerve block. (30th August 2019) - Kumita, S; Ueshima, H; Otake, H; Yamakage, M
Abstract : Background and aims: We previously reported a case of successive pain relief of gnathoplasty with an inferior alveolar nerve block and a maxillary nerve block under the ultrasound-guidance 1 . Gnathoplasty is an invasive jaw surgery with intense postoperative pain. Perioperative trigeminal nerve blocks can theoretically relief the pain for gnathoplasty. However, there have been few studies evaluating the spread of local analgesics of these blocks. We report a cadaveric study of an inferior alveolar nerve block with dye under the ultrasound-guidance. Methods: An inferior alveolar nerve block was performed with one soft cadaver. a high frequency linear probe was placed just below the zygomatic arch and the mouth was kept open to identify masseteric muscles clearly. a block needle was inserted in the out-of-plane technique and 5 mL of dye was injected to the pterygomandibular space, where an inferior alveolar nerve was included. Results: The injectate of nerve block were successfully spread around an inferior alveolar nerve and a lingual nerve, but did not reach to the mandibular nerve trunk. Conclusions: The present cadaveric study suggests that ultrasound-guided inferior alveolar nerve block can provide effective analgesia for gnathoplasty. Reference: Asian J Anesthesia. 2017; 55: 89–90